Pushing TC to 27.5 K in a heavy atom radical ferromagnet. Issue 96 (14th November 2016) - Lekin, Kristina; Ogata, Kazuma; Maclean, Adrian; Mailman, Aaron; Winter, Stephen M.; Assoud, Abdeljalil; Mito, Masaki; Tse, John S.; Desgreniers, Serge; Hirao, Naohisa; Dube, Paul A.; Oakley, Richard T.
Abstract : In the solid state the iodo-substituted bisdiselenazolyl radical1c orders as a bulk ferromagnet with T C = 10.5 K. With the application of pressure T C rises rapidly, reaching a value of 27.5 K at 2.4 GPa. Abstract : In the solid state the iodo-substituted bisdiselenazolyl radical1c orders as a ferromagnet with T C = 10.5 K. With the application of pressure T C rises rapidly, reaching a value of 27.5 K at 2.4 GPa. The accompanying structural and magnetic changes have been examined by high resolution powder X-ray diffraction and by DFT calculations of magnetic exchange interactions.